Programming of involvement of innovative technologies in training of members of the athletics team of Ukraine - Hutsol, Y.; Pylypei, L. (Slobozhanskyi herald of science and sport, 2020)
Purpose: theoretical and methodological substantiation of programming technology for the involvement of innovative technologies in the training process of the national team of Ukraine in athletics. Material and Methods: The research was carried out among athletes of the national team of Ukraine at the level not lower than the Master of Sports of Ukraine by conducting a questionnaire, self-experiment, pedagogical observation and pedagogical experiment.The total number of respondents is 43 athletes. Among the participants of the experiment are the winners of the Olympic Games and world championships, champions and winners of the European championships, champions of Ukraine. Results: The article presents programming as a rigidly determined system of sequential and time-tested operations within a certain time on the basis of the developed design of the control system. The algorithm for constructing a system for attracting innovative technologies to the preparation of athletes is carried out on the basis of regression analysis with numerical coefficients according to the formulas. Conclusions: the proposed programming technology makes it possible to create an effective system for constructing an individual training process in the national team of Ukraine in athletics.